A PILOT STUDY FOR THE FACTORS AFFECTING THE LEVEL OF FINANCIAL LITERACY AMONG STUDENTS IN UNIVERSITI PENDIDIKAN SULTAN IDRIS - Crister Kujat; Nur Yuhainis Ab Wahab (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Financial literacy is essential knowledge that everyone should acquire to make effective financial decisions. The quality of one’s life is frequently determined by one’s finances. Every financial choice is occasionally impacted by a circumstance in our lives. Therefore, the purpose of this pilot study is to evaluate the reability and validity of the research instrument on the factors that affect the level of financial literacy of students at Universiti Pendidikan Sultan Idris (UPSI). This research use a quantitative method to determine the factors that affect financial literacy. Researchers employ a stratified selection approach and simple random sampling technique to choose respondents. In this pilot study, the researcher used a minimum sample size of 30 respondents. The questionnaire is adapted from previous studies and distributed through Google form via email and Whatsapp. The data is collected and analyzed using the software tool Statistical Package For Social Science (SPSS) version 25.0. The findings of this pilot test show that Cronbach alpha is 0.942. This result show that the instrument is realiable and valid to use in the real study.